Capacidad antagónica de hongos celulolíticos frente a fusarium sp. y macrophomina sp. - Tarazona Meza, Néstor Leopoldo (2015)
This research aimed to evaluate the antagonistic activity of eight native cellulolytic fungi against the phytopathogenic fungi Fusarium sp. and Macrophomina sp. First, the promissory cellulolytic fungus strain was identified, for the purpose, the mycelial plugs (4 mm diameter) of pathogens and fungal antagonists were placed on the same dish at about 5 cm from each other. The antagonistic activity was determined by the level of mycoparasitism, competition for nutrients and space, recording the percentage of inhibition of the radial growth. A co-culture of the tested cellulolytic fungus strain that showed the best antagonistic activity and each pathogen strain was performed, then the colony forming units (CFU/ml-1 ) cultured in PDA were evaluated. They were also inoculated in pepper plants in pots to know the antagonistic potential. According the qualitative analysis, the strain A.O5 showed invasion and complete sporulation over the pathogens; while the co-culture inhibits the growth of pathogens at 96 h. The antagonistic activity was also showed against Fusarium and Macrophomina in pepper seedlings. The results showed that the A.O-5 strain is a potential antagonist for the pathogens evaluated.